Proteus mirabilis carrying NTEKPC-IId, blaNDM-1, blaOXA-10, aph(3')-VI, qnrD1 and IncQ and Col3M plasmids from a hospital in Recife-PE, Brazil (Research, Society and Development, 2021)
The present study objective to characterize the clinical aspects of a patient infected with two strains of P. mirabilis and the presence of resistance determinants in the two isolates from a patient at a public hospital in Recife-PE, Brazil. The total DNA of the isolates was extracted and submitted to PCR and amplicon sequencing for the investigation of resistance genes, blaKPC, blaOXA-10, blaOXA-23, blaOXA-48, blaOXA-58, blaVIM, blaIMP, blaSPM, blaGES, blaNDM, qnrD and aac(6')-Ib). Isolate P21-A2 harbored the aac(6')-Ib, blaOXA-10 and qnrD genes. One of the isolates, P20-A2, was selected for plasmid DNA sequencing. The results showed that the patient developed multiple infections with various pathogens including two strains of P. mirabilis. The patient was hospitalized for 103 days, had septic shock of skin, abdominal, pulmonary and ulcer focus, and died. Isolate P20-A2 harbored the genes blaNDM, qnrD, aph(3')-VI, blaKPC and blaOXA-10, and plasmids IncQ and Col3M, together with NTEKPC-IId. To our knowledge, this is the first report of P. mirabilis harboring NTEKPC-IId. Although P. mirabilis is standing out as a cause of nosocomial infections and a resistant multidrug pathogen, this species is still neglected, the emergence of these P. mirabilis isolates harboring aforementioned resistance determinants and the plasmids IncQ and Col3M demonstrate the potential for dissemination of important resistance genes, mainly in the case of P. mirabilis.